Research in the history of economic thought and methodology : including a symposium on religion, the Scottish Enlightenment, and the rise of liberalism - Fiorito, Luca; Scheall, Scott; Suprinyak, Carlos Eduardo; Ballor, Jordan J.; Matson, Erik W. (Emerald Publishing Limited, 2023)
Volume 41A of Research in the History of Economic Thought and Methodology features a symposium on "Religion, the Scottish Enlightenment, and the Rise of Liberalism," a new research essay by Syed Mohib Ali, and a roundtable on the institutionalist economics of Geoffrey Hodgson.
Keywords: Economics -- History.; Economics -- Methodology.; Smith, Adam, -- 1723-1790.; Hodgson, Geoffrey Martin, -- 1946-; Economics.; Business & Economics -- Economic History.; Economic history.; elektronické knihy; electronic books